The Influence of Social Media on University Students' Choice 0f Presidential Candidates in 2024 - Laurencia Primawati Degodona; Rajagukguk, Jonson; Sarumaha, Zeni Oktavianis (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2025)
Social media has become a primary tool in influencing voter decisions, especially among young generations, in the 2024 Election. With a creative and interactive approach, platforms such as TikTok dominate in delivering political messages to university students, who are part of the millennial and Gen Z generations. This research employs a quantitative descriptive method using questionnaires on 120 students from HKBP Nommensen University to measure the influence of social media on the decision to vote for presidential and vice-presidential candidates. The hypothesis test results indicate a significant influence of social media on students' voting decisions. 70.9% of respondents consider social media as the main factor influencing their choice, with TikTok being the most influential platform (74.2%). Additionally, entertaining and creative political slogans such as